A study on glycogen content of endometrial glands in infertile women - Karthik LR; Raja Parthiban S R; Savita D; Shruthi Neelakanth Shetageri (Journal of Pathology of Nepal)
Background: Infertility is a public health problem worldwide. One of the important factors involved in infertility is the poor quality of endometrium which leads to death of the ovum before and after implantation. Glycogen is known to be a direct source of nutrients for the early conceptus and its depletion may result in inadequate preparation of endometrium around the time of implantation and leading to infertility.